Męskocentryczny charakter współczesnej kultury polskiej w perspektywie koncepcji Geerta Hofstede`a. Wybrane aspekty problematyki = The male-oriented character of modern Polish culture in the perspective of Geert Hofstede`s conception: selected aspects of the issue - Arcimowicz, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The basic aim of the article is to analyze modern Polish culture with the use of Geert Hofstede`s theoretical proposition, which refers to the dimension of masculinity-femininity. The analysis covered selected aspects of such areas of social and cultural life, such as religion, politics, media, family, sexuality, job market, education. The executed analysis leads to the conclusion that Poland belongs to the category of masculine cultures.
Keywords: Hofstede, Geert (1928-2020); męskość; kobiecość; kultura polska; płeć; masculinity; femininity; Polish culture; gender